PEMBERIAN WARISAN ANAK LAKI-LAKI YANG MANUHOR MARGA/BELI MARGA BERDASARKAN HUKUM ADAT BATAK TOBA (STUDI DI KECAMATAN TARUTUNG KABUPATEN TAPANULI UTARA) - MESRI ELISABETH ARITONANG (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1.  Dr. Idha Aprilyana Sembiring, SH, MHum'2.  Dr. Edy Ikhsan, SH, MA3.  Dr. Rosnidar Sembiring, SH, MHumKindship system in Batakness community, especially on the Batak Toba community, is in Tarutung Sub-district, Tapanuli Utara Regency patrilineal realting to relationship to descent through the male line that will continue his father’s clan. The research problem are how about the rason for manuhor marga ceremony in the Batak Toba, how about the distribution of inheritance for a manuhor marga son according to the Batak toba law,and how about yhe resolution if there is a dispute in inheritance for a manuhor marga. The distribution of inheritance in Batak Toba tribe depends on Dalihan natolu wich state that a buying clan son is alegitime heir on his parent’s inheritance. When there is a dispute in inheritance, the settlement will be done through mon-litigation but through marhata ( family discussion) and adat body.